Dynamiczna Teoria Plastyczności Jako Pomost Miedzy Teoria Sprężystości a Teorią Plastyczności - Madejski, J. (Engineering Transactions, 1958)
It is shown on an example of prismatic rod with rectangular cross-section loaded with a simple bending moment, that it is possible to analyze the state of stress and strain by means of the dynamical theory of plasticity proposed by the author, if the state changes from elastic to plastic. In particular, at the initial moment of applying the load the state is elastic, while after an infinite period of time it becomes plastic (or elasto-plastic). The latter case is possible for sufficiently ductile materials only. For brittle materials, fracture occurs after a finite time and the corresponding stress distribution can be determined by means of the dynamical theory of plasticity. This problem is also treated in this paper.